AMIRAH, SINGLE PARENT: ANTARA DIALEKTIKA DAN NURANI KELUARGA - Fatawi, Fatawi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study explores the life dynamics of Amirah, a single mother who serves as the primary economic and emotional support for her extended family. Amirah is responsible not only for her two children but also for her siblings and nieces and nephews. Her economic activity as a street food vendor selling bakso pecel from her home porch symbolizes a micro-level class struggle, where family survival is sustained through perseverance, empathy, and familial solidarity. The aim of this research is to understand how Amirah negotiates her social position within the dialectics between economic struggle and family conscience, as well as how values of empathy and social responsibility shape the stability of her life. The study employs a qualitative approach using direct observation (fieldwork) and library research as the basis for a socio-empirical analysis. The findings indicate that although Amirah’s economic condition remains relatively static due to the heavy family burden, she manages to sustain her family’s livelihood through social strategies rooted in empathy and personal relationships with her customers. The dialectic between the desire for upward social mobility and the awareness of family responsibility forms the core dynamic reflecting the social reality of the lower class within a domestic economic context.